Dissimilar magnesium alloy composite structure and low-cost electric arc additive manufacturing method thereof
By employing functional partitioning design and interlayer friction stir processing technology, the interfacial bonding problem of AZ-based and rare earth magnesium alloy composite structures in arc additive manufacturing has been solved, achieving high-strength metallurgical bonding and low-cost manufacturing, which is suitable for aerospace and automotive lightweighting applications.
Patent Information
- Application Number
- CN202511738691.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-25
- Publication Date
- 2026-03-17
AI Technical Summary
When using existing electric arc additive manufacturing technology to prepare composite structures of AZ-based and rare earth magnesium alloys, defects such as incomplete fusion, porosity, and cracks are easily formed at the interface, resulting in the interfacial shear strength being less than 60% of the strength of the base material. Furthermore, introducing a transition layer increases the complexity and cost of the process.
By employing functional zoning design and interlayer friction stir processing technology, AZ-based and rare earth magnesium alloy materials are selected in different zones. Combined with single-arc sequential wire feeding and reciprocating cyclic deposition, the materials are deposited layer by layer and friction stir processing is performed at the interface to form a metallurgical bond without a transition layer.
A high-strength metallurgical bond of AZ-rare earth magnesium alloy composite structure was achieved, reducing material costs by more than 50%, improving interface bonding strength, enhancing forming quality, and avoiding the complexity and high cost of the transition layer.
Smart Images

Figure CN121670274A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of additive manufacturing, specifically relating to a dissimilar magnesium alloy composite structure and its low-cost arc additive manufacturing method. Background Technology
[0002] Magnesium alloys, as one of the lightest metallic structural materials, possess characteristics such as low density, high specific strength, good damping performance, and excellent electromagnetic shielding properties, demonstrating enormous application potential in aerospace, automotive lightweighting, and 3C electronics. However, single magnesium alloy materials often cannot meet the diverse performance requirements of complex service environments. For example, AZ / AM alloys (such as AZ31, AZ91, and AM60B) exhibit stable mechanical properties in the temperature range of 25-120℃, but their yield strength decreases by more than 50% at temperatures exceeding 150℃, making them unsuitable for high-temperature load-bearing components. In contrast, rare earth magnesium alloys (such as Mg-Gd-Y, Mg-Y-Nd, and Mg-Y-Zn series) form a high-melting-point, highly thermally stable second phase (such as Mg5Gd and Mg...) with the magnesium matrix due to the rare earth elements. 24 Y5 maintains high strength and creep resistance at 150-300℃, but its cost is about 4-6 times that of AZ / AM alloys, limiting its large-scale application.
[0003] Arc additive manufacturing technology is a directional energy deposition method based on wire. Using an electric arc as a heat source, it continuously melts metal wire and deposits it layer by layer according to a designed path to form a shape. It has advantages such as large forming size, low manufacturing cost, simple equipment, high material utilization and deposition efficiency. It is the main manufacturing method for high-quality and rapid forming of large metal components and has broad application prospects in the field of magnesium alloy component manufacturing.
[0004] However, when using arc additive manufacturing technology to directly form AZ-based composite structures with rare earth magnesium alloys, the differences in physical / chemical properties between the two types of alloys (such as a difference of 20-30% in the coefficient of thermal expansion and the tendency of rare earth elements to agglomerate at the interface to form brittle phases) lead to defects such as incomplete fusion, pores and cracks at the interface, and the interfacial shear strength is usually less than 60% of the strength of the base material.
[0005] Current solutions all require the introduction of a transition layer, but this increases process complexity, raises costs, and may introduce new interface reaction risks. Therefore, developing an additive manufacturing method that can achieve high-strength metallurgical bonding between AZ-based and rare-earth magnesium alloys without a transition layer, while also enabling controllable performance zoning and structural integration, has become a key technical problem that urgently needs to be solved in the development of lightweight, high-performance, and multifunctional integrated magnesium alloy components. Summary of the Invention
[0006] This invention addresses the problems existing in the prior art by providing a dissimilar magnesium alloy composite structure and its low-cost arc additive manufacturing method, which can achieve high-strength metallurgical bonding between AZ-based and rare earth magnesium alloys without a transition layer, and has broad application value.
[0007] To solve the above technical problems, the present invention provides the following technical solution: a method for arc additive manufacturing of dissimilar magnesium alloy composite structures, comprising the following steps:
[0008] Step (1): Select two materials: AZ series magnesium alloy wire and rare earth magnesium alloy wire;
[0009] Step (2): Based on the functional requirements of the component, the material allocation of the two types of wires is designed in zones, and the electric arc additive manufacturing process parameters, deposition sequence and additive path of the two types of materials are set respectively;
[0010] Step (3): Preheat the substrate, and select one of the two materials as material 1 and the other as material 2;
[0011] Step (4) First deposition of material 1: Using a single electric arc and sequential wire feeding method, the deposition of material 1 is completed first to form the first functional layer of the component;
[0012] Step (5): Intermediate material 2: Under the heat source of single electric arc melting electrode, continue to deposit material 2 on the surface of the first functional layer according to the partition design, process parameters and additive path determined in step 2, as a transition layer for subsequent friction stir processing;
[0013] Step (6): Interface treatment: After the component cools to room temperature, the top surface of the transition layer is milled to obtain a flat surface. Then, friction stirring is performed on the surface to refine the grains and improve the interfacial bonding performance.
[0014] Step (7): Final deposition of material 2: The component is preheated again, and material 2 is deposited on the surface after stirring and friction processing according to the parameters set in step (2) until the target thickness is reached, the second functional layer is completed, and the AZ-rare earth magnesium alloy composite structure is finally obtained.
[0015] Furthermore, in the aforementioned step (1), AZ series magnesium alloy wires and rare earth magnesium alloy wires with the same or different diameters of 1.0-1.6 mm are selected; the AZ series wires are AZ31, AZ61 or AZ91, and the rare earth magnesium alloy wires are Mg-Gd-Y, Mg-Y-Nd or Mg-Y-Zn alloys.
[0016] Furthermore, in the aforementioned step (2), the material allocation principle for the two types of wires is as follows: AZ series magnesium alloy is used in the service temperature ≤120℃ area, and rare earth magnesium alloy is used in the service temperature >120℃ area; the deposition sequence is as follows: first deposit m layers of AZ series magnesium alloy, and then deposit n layers of rare earth magnesium alloy on its top surface, or first deposit m layers of rare earth magnesium alloy, and then deposit n layers of AZ series magnesium alloy on its top surface, where m and n ≥ 1.
[0017] Further, the aforementioned step (3) specifically involves: removing oil and impurities from the surface of the substrate using alcohol and an angle grinder, and preheating the substrate to 200-250°C; the substrate is AZ31 or AZ91.
[0018] Furthermore, in the aforementioned steps (4), (5), and (7), the electric arc additive heat source is a molten electrode heat source, and the protective gas used in the additive process is argon gas with a purity greater than 99.9% and a gas flow rate of 15-20 L / min.
[0019] Furthermore, the electric arc additive manufacturing process parameters for the aforementioned AZ series magnesium alloys and rare earth magnesium alloys are independently controlled as follows: additive current 75-90A, wire feeding speed 6-8m / min, travel speed 0.2-0.3m / min, oscillation amplitude 3-8mm, and oscillation frequency 1.2-2.4Hz.
[0020] Furthermore, the aforementioned steps (4), (5) and (7) adopt a reciprocating cyclic stacking form during the stacking process to reduce the solidification difference at the end of the molten pool; a temperature measuring device is used to monitor the interlayer temperature after each additive process; the interlayer temperature of AZ series magnesium alloys is controlled at 150-200℃, and the interlayer temperature of rare earth magnesium alloys is controlled at 200-250℃.
[0021] In step (5), the specific number of deposition layers of material 2 needs to be determined according to the length of the stirring needle to ensure that the subsequent stirring friction processing can act on the interface between material 1 and 2.
[0022] Furthermore, in the aforementioned step (6), after the component cools to room temperature, a milling machine is used to remove 1-3 mm from the top surface of the transition layer to obtain a flat surface; then, 2-4 stirring friction processes are performed on the surface to break up the coarse brittle eutectic phase at the interface, refine the grains, repair cracks, and ensure the metallurgical bonding strength.
[0023] Furthermore, in the aforementioned interlayer friction stir machining, the shoulder diameter of the stirring head is 14-22mm, the stirring pin is a threaded cone with a root diameter of 7-10mm, a top diameter of 4-10mm, and a pin length of 4-7mm. The stirring head is made of hard alloys such as tungsten-rhenium alloy. During machining, the stirring head rotates at 300-1000 r / min, travels at 10-200 mm / min, and applies a downward pressure of 0.1-0.2mm. The stirring head has no tilt angle.
[0024] The present invention also provides a dissimilar magnesium alloy composite structure, which is prepared by any of the methods described in the present invention. The composite structure forms a metallurgical bond without a transition layer at the interface, and the service performance can be controlled by different zones.
[0025] Compared with the prior art, the beneficial technical effects of the present invention using the above technical solution are as follows:
[0026] (1) In terms of cost control, the present invention achieves the composite preparation of AZ-rare earth magnesium alloy through functional partition design. In the service temperature ≤120℃, the lower cost AZ-based magnesium alloy is used, and high-performance rare earth magnesium alloy is selected only in the critical area where the local heat load is >120℃. The amount of rare earth is drastically reduced, and the material cost is reduced by more than 50% compared with the all-rare earth structure.
[0027] (2) Regarding interface bonding, this invention innovatively introduces interlayer friction stir processing technology. By introducing friction stir processing between the two functional layers, the brittle eutectic phase is further broken up, the grains are refined and microcracks are healed, and a high-strength metallurgical bond is achieved. This fundamentally eliminates the hidden dangers of interface weakening of dissimilar materials and brittle phase aggregation, ensuring the overall mechanical properties and service safety.
[0028] (3) This invention uses only a conventional fused electrode arc additive manufacturing system, without relying on expensive transition materials or complex special equipment, to achieve integrated forming of large and complex bimetallic components. Combined with the strategy of "reciprocating cyclic stacking + interlayer temperature control", stress is controlled by path and microstructure is controlled by temperature, so as to achieve rapid manufacturing with no cracks, low deformation and high density. Attached Figure Description
[0029] Figure 1 This is a schematic diagram of the additive manufacturing path planning of the present invention.
[0030] Figure 2 This is a schematic diagram of the CMT arc additive manufacturing system used in Examples 1 and 2.
[0031] Figure 3 This is a schematic diagram of the stirring head used in the interlayer stirring friction treatment in Examples 1 and 2.
[0032] Figure 4Here is a schematic diagram of the macroscopic morphology of the formed component in Example 1: (a) is a front view of the additive component, and (b) is a top view of the additive component.
[0033] Figure 5 These are schematic diagrams of the microstructure of the components in Example 1; where (a1) is a schematic diagram of the microstructure of the AZ91 / WE43 composite interface under 200x magnification of an optical microscope, (a2) is a schematic diagram of the microstructure of the AZ91 / WE43 composite interface under 500x magnification of an optical microscope, (b1) is a schematic diagram of the microstructure of the AZ91 / WE43 composite interface under 1500x magnification of an electron microscope, and (b2) is a schematic diagram of the microstructure of the AZ91 / WE43 composite interface under 4000x magnification of an electron microscope.
[0034] Figure 6 This is a tensile curve of the component in Example 1 at room temperature.
[0035] Figure 7 Here are macroscopic morphological diagrams of the two components formed in Example 2: (a) is a front view of the straight arm component, and (b) is a front view of the elliptical ring component.
[0036] Figure 8 This is a tensile curve of the straight arm component in Example 2 at room temperature. Detailed Implementation
[0037] To better understand the technical content of the present invention, specific embodiments are described below in conjunction with the accompanying drawings.
[0038] In this invention, various aspects of the invention are described with reference to the accompanying drawings, in which numerous illustrative embodiments are shown. Embodiments of the invention are not limited to those depicted in the drawings. It should be understood that the invention is implemented through any of the various concepts and embodiments described above, as well as the concepts and embodiments described in detail below, because the concepts and embodiments disclosed herein are not limited to any particular implementation. Furthermore, some aspects of the invention disclosed may be used alone or in any suitable combination with other aspects of the invention disclosed.
[0039] This invention provides a method for arc additive manufacturing of dissimilar magnesium alloy composite structures, comprising the following steps:
[0040] Step (1): Select two materials: AZ series magnesium alloy wire and rare earth magnesium alloy wire;
[0041] Step (2): Based on the functional requirements of the component, the material allocation of the two types of wires is designed in zones, and the arc additive manufacturing process parameters, deposition sequence and additive path of the two materials are set respectively; the deposition sequence and material allocation are designed according to the actual service environment. AZ series magnesium alloy is used in the service temperature ≤120℃ area, and rare earth magnesium alloy is used in the >120℃ area; the additive manufacturing process parameters are determined according to the wire selected in step (1), including but not limited to additive current, additive speed, wire feeding speed, oscillation amplitude and oscillation frequency; the additive path is selected as interlayer reciprocating additive manufacturing to ensure the forming quality of the additive component.
[0042] Step (3): Preheat the substrate to 200-250°C: Before additive manufacturing, use alcohol and an angle grinder to remove oil and impurities from the substrate surface, and preheat the substrate to 200-250°C to reduce the tendency for thermal cracking; the substrate is a material with a chemical composition similar to that of the filament, such as AZ31 or AZ91; select one of the two materials as material 1 and the other as material 2.
[0043] Step (4) First deposition of material 1: Using a single arc and sequential wire feeding method, material 1 is deposited according to the partition design, process parameters and additive path determined in step (2). The protective gas is argon with a purity > 99.9%. A reciprocating cyclic stacking path is adopted. After each additive process is completed, the interlayer temperature is detected by a temperature measuring device. The temperature of AZ series magnesium alloy is controlled at 150-200℃, and the temperature of rare earth magnesium alloy is controlled at 200-250℃. After the interlayer temperature cools naturally to the target value, the welding torch is raised by one layer height and moved to the next layer arc starting position to continue additive processing. Layer by layer, the material is stacked to the design size to form the first functional layer of the component.
[0044] Step (5): Intermediate deposition of material 2: Under the single-arc melting electrode heat source, continue to deposit material 2 on the surface of the first functional layer according to the partition design, process parameters and additive path determined in step 2, as a transition layer for subsequent friction stir processing; wherein, the specific number of material 2 deposition layers needs to be determined according to the length of the stirring pin to ensure that the subsequent friction stir processing can act on the interface between material 1 and 2. Preferably, 2-3 layers of material 2 are deposited on the surface of the first functional layer.
[0045] Step (6): Interface treatment: After the component cools to room temperature, use a milling machine to remove 1-3mm from the top surface of the transition layer (the specific depth is adjusted according to the length of the stirring needle so that the needle tip trajectory can just cover the interface between the transition layer and the first functional layer) to obtain a flat surface; then perform 2-4 stirring friction processing on the surface to break the coarse brittle eutectic phase at the interface, refine the grains, repair cracks, and ensure metallurgical bonding strength.
[0046] Step (7): Final deposition of material 2: Place the component that has been treated at the interface and preheated to the target temperature (150-250℃) under a single electric arc melting electrode heat source, and continue to deposit material 2 according to the process parameters and path set in step (2); the protective gas is still argon gas with a purity greater than 99.9%, and the operation process is the same as step (4). Stack the layers to the design size to form the second functional layer, and finally obtain the AZ-rare earth magnesium alloy composite structure.
[0047] Controlling the interlayer temperature is also a key aspect of this invention. During the deposition of AZ series magnesium alloys, the interlayer temperature should ideally be maintained between 150-200℃: this range reduces heat accumulation and refines grains while preventing thermal cracking caused by temperatures below 100℃. When depositing rare-earth magnesium alloys, raising the interlayer temperature to 200-250℃ can reduce residual stress without significantly coarsening the grains, promoting a uniform transition between the two sides of the microstructure, thereby achieving continuous performance gradients and integrated microstructure in the bimetallic composite structure.
[0048] In this application, the term "room temperature" means 25±5℃.
[0049] Example 1:
[0050] A straight-arm AZ91-WE43 composite structural component was formed using a CMT (Continuous Metal-Injection) arc additive manufacturing system. The resulting component is 85mm high, 140mm long, and 14mm wide. The CMT system, as shown in Figure 2, consists of two Fronius CMT-Advanced4000 welding power sources (with built-in water cooling systems), an ABB six-axis industrial robot and its control cabinet, and a wire feeding system. A dual-wire CMT welding torch is fixed to the end of the robot's sixth axis. Interlayer friction stir machining utilizes a tungsten-rhenium alloy stirring head. Figure 3 As shown, the shoulder diameter is 18mm, the stirring needle is a threaded cone with a root diameter of 8mm, a top diameter of 5mm, and a needle length of 5mm.
[0051] The specific steps are as follows:
[0052] Step 1: Select AZ91 and WE43 wires, both with a diameter of 1.2mm. The mass percentages of each element in the AZ91 wire are as follows: Al ~8.62, Mn ~0.55, Zn ~0.33, Mg balance; the mass percentages of each element in the WE43 wire are as follows: Y ~3.82, Nd ~2.46, Zr ~0.56, Mg balance.
[0053] Step Two: Based on the functional requirements of the component, the material allocation of the two types of wires is designed in zones, and the arc additive manufacturing process parameters, deposition sequence, and additive manufacturing path are set for each material. The additive manufacturing process parameters are determined based on the wire diameter test in Step One. AZ91: Additive current 75A, wire feed speed 8m / min, travel speed 0.24m / min, oscillation amplitude 5mm, oscillation frequency 2.2Hz; WE43: Additive current 75A, wire feed speed 8m / min, travel speed 0.24m / min, oscillation amplitude 5mm, oscillation frequency 1.4Hz; The protective gas during the additive manufacturing process is 99.9% pure argon, the protective gas flow rate is 20L / min, the single-layer height of the deposited layer is approximately 3mm, and the width is approximately 14mm. The deposition sequence is to first deposit 16 layers of AZ91 on the substrate, and then deposit 12 layers of WE43 on AZ91. The component additive manufacturing path is a reciprocating cyclic stacking, and the schematic diagram of the additive manufacturing path is shown in Figure 1.
[0054] Step 3: Preheat the substrate to 250°C: The substrate used for additive manufacturing is an AZ91 substrate with dimensions of 250mm×480mm×8mm. Before additive manufacturing, use alcohol and an angle grinder to remove oil and impurities from the surface of the substrate, and preheat the substrate to 250°C to reduce the tendency for thermal cracking.
[0055] Step 4: First deposition (AZ91): Under the single arc melting electrode heat source, AZ91 is deposited according to the process parameters and additive path set in step (2). After each additive layer is completed, the interlayer temperature is monitored by a temperature measuring device and kept at 150-200℃. After the interlayer temperature cools down to the target value naturally, the welding torch is raised by 3mm and moved to the arc starting position of the next layer for additive. The machine is stopped after the 16th layer of AZ91 is deposited.
[0056] Step 5: Intermediate deposition (WE43): Under the single arc melting electrode heat source, continue to deposit 2 layers of WE43 on the top surface of AZ91 according to the partition design, process parameters and additive path determined in step (2) as a transition layer for subsequent friction stir processing;
[0057] Step 6: Interface treatment: After the component has cooled to room temperature, first remove 1mm of the top layer of WE43 with a milling machine, and then perform three consecutive interlayer stirring friction processing at the same interface: stirring head speed 800r / min, travel speed 10mm / min, downward pressure 0.1mm, and tilt angle 0°.
[0058] Step 7: Final Deposition (WE43): The component is reheated to 220°C. Under a single-arc fusion electrode heat source, WE43 is deposited on the treated interface according to the process parameters and path set in step (2). After each deposition, the temperature is measured and maintained at 200-250°C. After natural cooling to the target value, the welding torch is raised by 3mm and moved to the next layer to start the arc. After a total of 12 layers are deposited, the machine is stopped. The morphology of the obtained AZ91 / WE43 composite component is shown in the figure. Figure 4 .
[0059] Figure 5 The microstructure at the interface between AZ91 and WE43 in the middle of the component is shown in the figure. (a1) shows the microstructure morphology of the AZ91 / WE43 composite interface under 200x optical microscopy; (a2) shows the microstructure morphology of the AZ91 / WE43 composite interface under 500x optical microscopy; (b1) shows the microstructure morphology of the AZ91 / WE43 composite interface under 1500x electron microscopy; and (b2) shows the microstructure morphology of the AZ91 / WE43 composite interface under 4000x electron microscopy. The grain sizes on both sides of the interface differ significantly, with the AZ91 side approximately 40 μm and the WE43 side approximately 10 μm. The AZ91 region consists of an α-Mg matrix, coarse supersaturated eutectic α-Mg phases at the grain boundaries, and elongated β-Mg... 17 Al 12 and a small amount of white granules The composition is Al8Mn5, consistent with the depositional microstructure of pure AZ91. In the WE43 region, besides the α-Mg matrix, a large amount of granular eutectic Mg is distributed at the grain boundaries. 24 Y5 and a small amount of needle-like Mg 14 The Nd2Y structure is consistent with the depositional microstructure of pure WE43 material. Furthermore, a fine-grained band forms at the interface, and numerous flocculent phases with the composition Mg8Al2(Y,Nd) are present inside, which is due to the interdiffusion of the two alloying elements during deposition. Figure 6 The tensile curves of the AZ91 / WE43 bimetallic composite structure specimen at room temperature are shown. It can be seen that the tensile strength in the direction of travel of the component reaches 262 MPa, and the elongation after fracture is 14.38%, exhibiting a good balance between strength and plasticity.
[0060] Example 2
[0061] Two VWZ831K-AZ91 composite components were formed using a CMT (Continuous Metal-Induced Mass Manufacturing) system: one is a straight arm component measuring 300mm × 300mm × 14mm, and the other is an elliptical ring component with a major axis of 300mm, a minor axis of 150mm, a height of 300mm, and a thickness of 14mm. The CMT system, as shown in Figure 2, consists of two Fronius CMT-Advanced 4000 welding power supplies (with built-in water cooling systems), an ABB six-axis industrial robot and its control cabinet, and a wire feeding system. A dual-wire CMT welding torch is fixed to the end of the robot's sixth axis. The interlayer friction stir machining (FSM) used a tungsten-rhenium alloy stirring head (Figure 3) with a shoulder diameter of 18mm. The stirring needle is a threaded cone with a root diameter of 8mm, a top diameter of 5mm, and a needle length of 5mm.
[0062] The specific steps are as follows:
[0063] Step 1: Select AZ91 and VWZ831K wires, both with a diameter of 1.2mm. The mass percentages of each element in the AZ91 wire are as follows: Al ~8.62, Mn ~0.55, Zn ~0.33, Mg balance; the mass percentages of each element in the VWZ831K wire are as follows: Gd ~7.80, Y ~3.07, Zn ~0.57, Zr ~0.56, Mg balance.
[0064] Step Two: Based on the functional requirements of the component, the material allocation of the two types of wires is designed in zones, and the arc additive manufacturing process parameters, deposition sequence, and additive manufacturing path are set for each material respectively: The additive manufacturing process parameters are determined based on the wire diameter test in Step One. AZ91: Additive current 75A, wire feed speed 8m / min, travel speed 0.24m / min, oscillation amplitude 5mm, oscillation frequency 2.2Hz; VWZ831K: Additive current 80A, wire feed speed 8m / min, travel speed 0.24m / min, oscillation amplitude 5mm, oscillation frequency 2.2Hz; The protective gas in the additive manufacturing process is 99.9% pure argon, the protective gas flow rate is 20L / min, the single layer height of the deposited layer is approximately 3mm, and the width is approximately 14mm. For different components, the specific deposition sequence and path settings are as follows: Straight arm component: First, deposit 100 layers of VWZ831K on the substrate, and then continue to deposit 100 layers of AZ91 on it. The additive manufacturing path adopts a reciprocating cyclic stacking method. Elliptical ring component: First, 80 layers of VWZ831K are deposited on the substrate, followed by 120 layers of AZ91. The additive path of the component is an ellipse with major and minor axes of 300mm and 150mm, respectively. The path planning is based on a cycle of 10 layers. In each cycle, the first 5 layers are deposited in a clockwise direction, and the last 5 layers are deposited in a counterclockwise direction. The arc start / extinguishing points of each layer in one cycle are uniformly staggered along the closed ellipse.
[0065] Step 3: Preheat the substrate to 250°C: The substrate used for additive manufacturing is an AZ91 substrate with dimensions of 250mm×480mm×8mm. Before additive manufacturing, use alcohol and an angle grinder to remove oil and impurities from the surface of the substrate, and preheat the substrate to 250°C to reduce the tendency for thermal cracking.
[0066] Step 4: First deposition (VWZ831K): Under the single arc melting electrode heat source, deposit VWZ831K according to the process parameters and additive path set in step (2), and use a temperature measuring device to monitor the interlayer temperature after each additive layer is completed, and keep it at 200-250℃; after the interlayer temperature cools down to the target value naturally, raise the welding torch by 3mm and move it to the arc starting position of the next layer for additive layer until the VWZ831K area in the two components reaches the design height and then stop the machine.
[0067] Step 5: Intermediate deposition (AZ91): Under the single arc melting electrode heat source, continue to deposit 2 layers of AZ91 on the top surface of VWZ831K according to the partition design, process parameters and additive path determined in step (2), as a transition layer for subsequent friction stir processing;
[0068] Step 6: Interface treatment: After the component has cooled to room temperature, first use a milling machine to remove 1mm from the top layer of VWZ831K, and then perform three consecutive interlayer stirring friction processing at the same interface: stirring head speed 800r / min, travel speed 10mm / min, downward pressure 0.1mm, and tilt angle 0°.
[0069] Step 7: Secondary Deposition (AZ91): The component is reheated to 200℃, and AZ91 is deposited on the treated interface under a single arc melting electrode heat source according to the process parameters and path set in step (2). After each deposition, the temperature is measured and maintained at 150-200℃ between layers. After natural cooling to the target value, the welding torch is raised by 3mm and moved to the next layer to start the arc. The cumulative deposition is stopped after reaching the target height. The morphology of the two VWZ831K-AZ91 composite components obtained is as follows. Figure 7 As shown in the figure. In the figure, (a) is the front view of the straight arm component, and (b) is the front view of the elliptical ring component. The tensile curve of the VWZ831K-AZ91 bimetallic composite straight arm component at room temperature is shown below. Figure 8 As shown, the mechanical properties of the component do not exhibit significant anisotropy in the direction of travel and deposition. In the direction of travel, the tensile strength can reach 247 MPa, with an elongation after fracture of 13.75%; in the direction of deposition, the tensile strength can reach 242 MPa, with an elongation after fracture of 12.03%.
[0070] This invention utilizes low-cost AZ series magnesium alloy welding wire and high-performance rare-earth magnesium alloy welding wire, and designs the two materials in zones according to their service temperature. Through a synergistic process of "single-arc sequential wire feeding + interlayer friction stir machining," reliable metallurgical bonding can be achieved without a transition layer. The formed component combines the high plasticity of AZ alloys with the high strength and heat resistance of rare-earth alloys, enabling the rapid and low-cost manufacture of large dissimilar magnesium alloy composite structures. This provides a short-cycle, high-performance integrated solution for aerospace and automotive lightweighting, meeting the diverse material performance requirements of complex working conditions, and has broad application prospects.
[0071] While the present invention has been described above with reference to preferred embodiments, it is not intended to limit the invention. Those skilled in the art can make various modifications and refinements without departing from the spirit and scope of the invention. Therefore, the scope of protection of the present invention shall be determined by the claims.
Claims
1. A method of arc additive manufacturing of a composite structure of dissimilar magnesium alloys, characterized in that, Comprising the following steps: Step (1): Selecting two materials: AZ series magnesium alloy wire and rare earth magnesium alloy wire; Step (2): According to the functional requirements of the component, the material distribution of the two wire materials is partitioned and designed, and the electric arc additive process parameters, deposition sequence and additive path of the two materials are set respectively; Step (3): Preheat the substrate, select one of the two materials as material 1 and the other as material 2; Step (4) First deposit material 1: using single arc, sequential wire feeding method, first complete the deposition of material 1, form the first functional layer of the component; Step (5): Intermediate deposition of material 2: under the single arc consumable heat source, continue to deposit material 2 on the surface of the first functional layer according to the partition design, process parameters and additive path determined in step 2, as the transition layer for subsequent friction stir processing; Step (6): Interface processing: after the component cools to room temperature, the top surface of the transition layer is milled to obtain a flat surface, and then friction stir processing is performed on the surface to refine the grains and improve the interface bonding performance; Step (7): Final deposition of material 2: reheat the component, continue to deposit material 2 on the surface after friction stir processing according to the parameters set in step (2), until the target thickness is reached, complete the construction of the second functional layer, and finally obtain an AZ-rare earth magnesium alloy composite structure.
2. The method according to claim 1, wherein In step (1), AZ series magnesium alloy wires with diameters of 1.0-1.6 mm and rare earth magnesium alloy wires with diameters of 1.0-1.6 mm are selected, which have the same diameter or different diameters; the AZ series wires are AZ31, AZ61 or AZ91, and the rare earth magnesium alloy wires are Mg-Gd-Y, Mg-Y-Nd or Mg-Y-Zn series alloys.
3. The method of claim 1, wherein the method is a hybrid magnesium alloy composite structure arc additive manufacturing method. In step (2), the material distribution principle of the two wire materials is: AZ series magnesium alloy is used in the region with a service temperature ≤120℃, and rare earth magnesium alloy is used in the region with a temperature >120℃; the deposition sequence is: first deposit m layers of AZ series magnesium alloy, then deposit n layers of rare earth magnesium alloy on the top surface of the AZ series magnesium alloy, or first deposit m layers of rare earth magnesium alloy, then deposit n layers of AZ series magnesium alloy on the top surface of the rare earth magnesium alloy, m, n ≥1.
4. The method of claim 1, wherein the method is a hybrid magnesium alloy composite structure arc additive manufacturing method. In step (3), the specific steps are: use alcohol and an angle grinder to remove oil stains and impurities on the surface of the substrate, and preheat the substrate to 200-250℃; the substrate is AZ31 or AZ91.
5. The method of claim 1, wherein the method is a hybrid magnesium alloy composite structure electric arc additive manufacturing method. In steps (4), (5) and (7), the arc additive heat source is a consumable heat source, and the protective gas used in the additive process is argon with a purity of more than 99.9%, and the gas flow is 15-20 L / min.
6. The method of claim 1, wherein the method is a hybrid magnesium alloy composite structure electric arc additive manufacturing method. The electric arc additive process parameters of AZ series magnesium alloy and rare earth magnesium alloy are independently controlled as follows: additive current 75-90 A, wire feeding speed 6-8 m / min, travel speed 0.2-0.3 m / min, swing amplitude 3-8 mm, and swing frequency 1.2-2.4 Hz.
7. The method of claim 1, wherein the method is a hybrid magnesium alloy composite structure electric arc additive manufacturing method. Steps (4), (5) and (7) are in the form of reciprocating cycle accumulation during the accumulation process to reduce the solidification difference at the end of the molten pool; a temperature measuring device is used to monitor the interlayer temperature after each increment; the interlayer temperature of AZ series magnesium alloy is controlled at 150-200℃, and the interlayer temperature of rare earth magnesium alloy is controlled at 200-250℃. In step (5), the specific deposition layer number of material 2 needs to be determined according to the length of the stirring needle to ensure that the subsequent friction stir processing can act on the interface between materials 1 and 2.
8. The method of claim 1, wherein the method is a hybrid magnesium alloy composite structure electric arc additive manufacturing method. In step (6), after the component is cooled to room temperature, the top surface of the transition layer is removed by 1-3mm using a milling machine to obtain a flat surface; then 2-4 times of friction stir processing is performed on the surface to break the coarse brittle eutectic phase at the interface, refine the grains, repair the cracks, and ensure the metallurgical bonding strength.
9. The method of claim 1, wherein the method is a hybrid magnesium alloy composite structure electric arc additive manufacturing method. In the interlayer friction stir processing, the shoulder diameter of the stirring head is 14-22mm, the stirring needle is a threaded cone, the root diameter of the stirring needle is 7-10mm, the top diameter is 4-10mm, the needle length is 4-7mm, and the material of the stirring head is tungsten-rhenium alloy or other hard alloy; the rotation speed of the stirring head is 300-1000r / min, the travel speed is 10-200mm / min, the pressing amount is 0.1-0.2mm, and the stirring head has no inclination angle.
10. A composite structure of dissimilar magnesium alloys, characterized by, The composite structure is prepared by the method of any one of claims 1-9, forms a metallurgical bond without an excessive layer at the interface, and the service performance partition is controllable.
Citation Information
Cited By
Double-additive-process collaborative manufacturing method and system based on forming area characteristics
CN122077342A